Education of the Health Culture for Future Teacher's Personality - Olena Momot; Serhii Novik; Yevheniia Shostak; Olena Zhdanova-Nedilko (Educational Challenges)
The purpose of the article is to substantiate the process of educating the health culture of a future teacher.